Epilepsy of infancy with migrating focal seizures in a patient with nonketotic hyperglycinemia - Anuar, Muhamad Azamin; Syed Ahmad Shihabuddin Abdurrahman Alsagoff, Sharifah Aishah; Mohamed, Ahmad Rithauddin; Murugesu, Sumitha (Korean Child Neurology Society, 2022)
Nonketotic hyperglycinemia (NKH) is an inborn error of glycine metabolism leading to refractory epilepsy and severe developmental delays. It is caused by autosomal recessive inheritance of a defect in the glycine cleavage system in the mitochondrial enzymatic complex pathway [1]. This defect leads to overstimulation of the N-methyl-D-aspartate receptor and neurological damage due to glycine accumulation in all body compartments. The typical presentation of NKH is progressive encephalopathy, apnea, and seizures during the neonatal period [2]. Those who survive the neonatal period progress into refractory seizures with moderate to severe cognitive impairment. Apart from antiseizure medications, sodium benzoate, dextromethorphan, and a ketogenic diet, no known therapy is effective in treating this condition [3]. Electroencephalography (EEG) is used to assess brain and seizure activity in NKH. The usual patterns seen are burst-suppression, hypsarrhythmia, and multifocal epileptiform activity [4,5]. Epilepsy of infancy with migrating focal seizures (EIMFS) in NKH has never been described in the literature. We report a case of a severe form of NKH presenting during the neonatal period that showed a burst-suppression EEG pattern and evolved into EIMFS